Notes on growing a tree in a graph. Issue 2 (18th December 2018) - Devroye, Luc; Dujmović, Vida; Frieze, Alan; Mehrabian, Abbas; Morin, Pat; Reed, Bruce
Abstract : We study the height of a spanning tree T of a graph G obtained by starting with a single vertex of G and repeatedly selecting, uniformly at random, an edge of G with exactly one endpoint in T and adding this edge to T .